New sieges on the oral tradition of l - Rivera Andía, Juan Javier (2025)
This book consists of three parts, each of considerable length. The first is dedicated to the verbal art of Rapaz (Sierra de Lima, Peru). The second (signed solely by Luis Andrade) focuses on the dialectal and historical aspects of Rapacino Quechua. The third, and largest, part transcribes and presents a corpus of collected ritual songs and theatrical speeches. As a whole, the book constitutes a valuable source of information on these forms of Andean oral tradition, especially their linguistic aspects and their dimensions related to the use of space.